Bài $1.1.\\\\ 2x^2+5x-1 = 7\sqrt{x^3-1}$

Bài $1.2.\\\\ 3\sqrt{x-1}+2\sqrt{x+1} = 5\sqrt[4]{x^2-1}$

Bài $1.3.\\\\ 3\sqrt{x^2+4x-5}+\sqrt{x-3} = \sqrt{11x^2+25x+2}$

Bài $1.4.\\\\ 2x^2-2x+2=3\sqrt{(x-2)(x^2+x)}$

Bài $1.5.\\\\ 4x^2-4x-10 = \sqrt{8x^2-6x-10}$

Bài $1.6.\\\\ \sqrt{2x^2+3x+1} - \sqrt{2x^2-2} = x+1$

Bài $1.7.\\\\ x^3+1=2\sqrt[3]{2x-1}$

Bài $1.8.\\\\ x+3(2-3x^2)^2=2$

Bài $1.9.\\\\ 2x^2-5x+2=4\sqrt{2(x^3-21x-20)}$

Bài $1.10.\\\\ \sqrt[3]{7x+1} -\sqrt[3]{x^2-x-8}+\sqrt[3]{x^2-8x-1} = 2$

Bài $1.11.\\\\ x+\sqrt{13-x^2}+x\sqrt{13-x^2} = 11$

Bài $1.12.\\\\ \sqrt[4]{18-x}+\sqrt[4]{x-79} = 5$


Bài $2.1.\\\\ x+1+\sqrt{x^2-4x+1} = 3\sqrt{x}$

Bài $2.2.\\\\ \sqrt{x^2-\frac{7}{x^2}}+\sqrt{x-\frac{7}{x^2}} = x$

Bài $2.3.\\\\ \dfrac{x-\sqrt{x}}{1-\sqrt{2(x^2-x+1)}} = 1$

Bài $2.4.\\\\ (x+2+3\sqrt{x})(x+18+9\sqrt{x}) = 15$

Bài $2.5.\\\\ 8x-27-4\sqrt{3x-2}-24\sqrt{x-4} = 0$

Bài $2.6.\\\\ x+\sqrt{x-1} = 3+\sqrt{2(x^2-5x+8)}$

Bài $2.7.\\\\ \sqrt{3x+1} - \sqrt{6-x}+3x^2-14x-8 = 0$

Bài $2.8.\\\\ 1+\sqrt{x+1} = 4x^2+\sqrt{3x}$

Bài $2.9.\\\\ \sqrt{x-2}+\sqrt{4-x} = 2x^2-5x-1$

Bài $2.10.\\\\ \sqrt{5x-1}+\sqrt[3]{9-x} = 2x^2+3x - 1$

Bài $2.11.\\\\ 4x-x^2 =3\sqrt{4-3\sqrt{10-3x}}$


Bài $3.1.\\\\ \sqrt{2x^2+5x+12}+\sqrt{2x^2+3x+2} = x+5$

Bài $3.2.\\\\ x+3\sqrt{5-x} = 1+3\sqrt{x-1}+\sqrt{(5-x)(x-1)}$

Bài $3.3.\\\\ \sqrt{\dfrac{1-x}{x}} = \dfrac{2x+x^2}{1+x^2}$

Bài $3.4.\\\\ x^2+x+12\sqrt{x+1} = 36$

Bài $3.5.\\\\ (4x-1)\sqrt{x^2+1} = 2x^2+2x+1$

Bài $3.6.\\\\ \sqrt{x-2}+\sqrt{4-x} = x^2-6x+11$

Bài $3.7.\\\\ 2\sqrt{3x+4}+3\sqrt{5x+9} = x^2+6x+13$

Bài $3.8.\\\\ 2 - \dfrac{x^2}{4} = \sqrt{1-x}+\sqrt{1+x}$

Bài $3.9.\\\\ x\sqrt{2x^2+5x+3} = 4x^2-5x-3$

Bài $3.10.\\\\ 3x^2-8x+3 - 3\sqrt{x+1} = 0$

Bài $3.11.\\\\ 4\sqrt{x+2}+\sqrt{22-3x} = x^2+8$

Bài $3.12.\\\\ \sqrt{x+3}+\dfrac{4x}{\sqrt{x+3}} = 4\sqrt{x}$

Bài $3.13.\\\\ \dfrac{x^3-2x}{x^2-1-\sqrt{x^2-1}} = \sqrt{3}$

Bài $3.14.\\\\ \sqrt{1+x^2+x^4}+x = \sqrt{x - x^3}$

Bài $3.15.\\\\ \sqrt{2x^2+x+6}+\sqrt{x^2+x+2} = x+\dfrac{4}{x}$

Bài $3.16.\\\\ 2x^2-11x+21 = 3\sqrt[3]{4x-4}$

Bài $3.17.\\\\ 2x^2-6x-1 =\sqrt{4x+5}$

Bài $3.18.\\\\ 2\sqrt{x^2-2x-1}+\sqrt[3]{x^3-14} = x - 2$

Bài $3.19.\\\\ (6x-5)\sqrt{x+1}-(6x+2)\sqrt{x-1}+4\sqrt{x^2-1} = 4x - 3$

Bài $3.20.\\\\ (4x-1)\sqrt{3-2x}+(7-4x)\sqrt{2x-1}=2\sqrt{-4x^2+8x-3}+4$



Bài $4.1.\\\\ \sqrt{x}+\sqrt{x-5} = x^2-5x+7$

Bài $4.2.\\\\ x^2-4x-3 = \sqrt{x+5}$

Bài $4.3.\\\\ \sqrt{3x+1} = -4x^2+13x - 5$

Bài $4.4.\\\\ 4\sqrt{x+1} -1 = 3x+2\sqrt{x-1}+\sqrt{1-x^2}$

Bài $4.5.\\\\ 2\sqrt{x^2+3} - \sqrt{8+2x-x^2} = x$

Bài $4.6.\\\\ x- 5(5x^2-1)^2 = -1$

Bài $4.7.\\\\ \sqrt[3]{x-2} = 8x^3-60x^2+151x-128$

Bài $4.8.\\\\ \sqrt[3]{3x+1}+\sqrt[3]{5-x}+\sqrt[3]{2x-9}-\sqrt[3]{4x-3} = 0$

Bài $4.9.\\\\ \sqrt[4]{1-x^2}+\sqrt[4]{1-x}+\sqrt[4]{1+x} = 3$

Bài $4.10.\\\\ \sqrt{3x^2+6x+7}+\sqrt{5x^2+10x+14} = 4 - 2x - x^2$

Bài $4.11.\\\\ 4x^2+7x+1=2\sqrt{x+2}$

Bài $4.12.\\\\ 2(2\sqrt{1+x^2}-\sqrt{1-x^2})-\sqrt{1-x^4} = 3x^2+1$

Bài $4.13.\\\\ x^2\sqrt[4]{2-x^4}-1 = x^4-x^3$

Bài $4.14.\\\\ (x^2+x+1)^3+3 = 10\sqrt[3]{10(x^2+x+1)-3}$

Bài $4.15.\\\\ \sqrt{x^2-2x+5}+\sqrt[3]{2x^2-4x+10} = -x^2+2x+1$